Reconstructing Sharia Competent Notarial Authority in Indonesia: Legal Pluralism and Gender Justice in Islamic Family Law - Chaerul Anwar; Abdullah Sulaiman; Yayan Sopyan (Universitas Muhammadiyah Bandung, 2025)
This study examines the structural position of notarial authority within Indonesia’s plural Islamic family law system, particularly the tension between formal authenticity under civil law and substantive compliance with Islamic legal principles. In practice, notarial deeds in family matters such as marriage agreements, inheritance arrangements, and marital property settlements possess strong evidentiary value, yet their conformity with Islamic legal norms is not always ensured in Religious Court adjudication. Despite the growing involvement of notaries in family-related legal documentation, limited scholarship has addressed the institutional gap between civil notarial authority and Sharia compliance standards in Indonesia’s Islamic family law governance. This study therefore investigates how Religious Courts assess notarial deeds in Islamic family law disputes and what regulatory framework is required to ensure both legal validity and Sharia compliance. Using a qualitative normative–doctrinal approach, the research analyzes statutory regulations alongside selected Religious Court decisions from 2019–2023. The findings reveal a regulatory and professional competency gap: although notaries are authorized to draft authentic deeds, courts frequently conduct substantive review to evaluate Sharia compliance, gender implications, and distributive justice. Theoretically, this study contributes to socio-legal scholarship on Islamic legal pluralism by conceptualizing a model of Sharia-Competent Notarial Authority integrating maqāṣid al-sharīʿah and gender justice perspectives. The study recommends incorporating mandatory Sharia competency standards for notaries involved in Islamic family law documentation to strengthen legal certainty and religious legitimacy.